PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF MENGGUNAKAN GENIALLY PADA MATA PELAJARAN ILMU PENGETAHUAN ALAM DAN SOSIAL - Melati Putri, Indah; Mulyawati, Yuli; Saeful Zen, Dendy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research uses the Research and Development (R&D) method with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). This research involved one lecturer each of media experts, linguists, material experts, and involved one teacher. The subjects in this study were fifth grade teachers and fifth grade students of SDN Sirnagalih 03 Bogor Regency in the academic year 2023/2024 with a total of 27 students. From the results of this study it can be concluded that interactive learning media using genially is suitable for use in learning. This is based on the results of validation conducted by validators obtained the final results of validation of media experts by 88%, language experts by 100%, lecturer material experts by 100%, and teacher material experts by 87% with an average result of 93% which is included in the "Worthy" criteria. As well as based on the results of the student participant response questionnaire which obtained a result of 96% and the teacher who obtained 100%, both of which were classified as "Feasible" criteria applied in learning.